Short-term influence of prednisone and phenobarbital on thyroid function in euthyroid dogs. - Daminet, S (1999)
The short-term effects of prednisone and phenobarbital on serum total thyroxine (tT4), free thyroxine (fT4), and thyroid stimulating hormone (TSH) were evaluated in euthyroid dogs. Twenty-six beagles were randomly divided into 3 groups receiving, respectively, a placebo, prednisone (1.2 to 2 mg/kg body weight, per os, every 12 hours for 3 weeks), or phenobarbital (1.8 to 3 mg/kg body weight for 1 week, then 2.7 to 4.5 mg/kg body weight, per os, every 12 hours for 2 weeks). Blood samples taken over a 6-week period were assayed for serum tT4, fT4, and TSH. Phenobarbital therapy in our study did not affect serum tT4, fT4, or TSH concentrations. Prednisone therapy, however, significantly decreased serum tT4 and fT4, but did not affect serum TSH concentrations.